NORDSCI Conference Proceedings 2021 Book 1, Volume 4 2021
DOI: 10.32008/nordsci2021/b1/v4/03
|View full text |Cite
|
Sign up to set email alerts
|

Competence to Design and Plan Education and Its Application in School Practice

Abstract: "Planning is an essential part of the preparation and implementation of the teaching process. Designing and planning education is an important part of the complex professional competencies of teachers, which were the subject of several years of research carried out at the University of Constantine the Philosopher in Nitra. Scientific research of Slovak experts focused on the issue of the professional competencies of teachers. The starting point was to determine the current state of professional skills of teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This contradicts most researchers such as Yang and Chang (2023), Baba Rahim (2022), Geletu (2022), Jarrahzade and Mohamadi Zenouzagh (2022) revealed that teacher competence significantly predicted engagement. Other studies such as Eton et al (2019), Predanocyová and Jonášková (2021), Tohidian and Nodooshan (2021), Pratiwi et al (2020), Nagro et al (2019) also reported that teacher competence significantly influenced engagement. Nonetheless, the findings also indicated that teacher competence positively and negatively predicted engagement.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This contradicts most researchers such as Yang and Chang (2023), Baba Rahim (2022), Geletu (2022), Jarrahzade and Mohamadi Zenouzagh (2022) revealed that teacher competence significantly predicted engagement. Other studies such as Eton et al (2019), Predanocyová and Jonášková (2021), Tohidian and Nodooshan (2021), Pratiwi et al (2020), Nagro et al (2019) also reported that teacher competence significantly influenced engagement. Nonetheless, the findings also indicated that teacher competence positively and negatively predicted engagement.…”
Section: Discussionmentioning
confidence: 88%
“…Studies (Yang & Chang, 2023;Baba Rahim, 2022;Geletu, 2022;Jarrahzade & Mohamadi Zenouzagh, 2022;Eton et al, 2019;Predanocyová & Jonášková, 2021;Tohidian & Nodooshan, 2021;Pratiwi et al, 2020;Nagro et al, 2019) have examined the link between teacher competence and engagement. However, contextual and conceptual gaps emerged from the aforementioned studies.…”
Section: Empirical Review Teacher Competence and Engagementmentioning
confidence: 99%
See 1 more Smart Citation